Kontruksi Sistem Jaminan Sosial dalam Perspektif Ekonomi Islam - Aprianto, Naerul Edwin Kiky (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2017)
This article intends to examine the social security system in the perspective of Islamic economy. Using literature review, this article cut social security. For that, it can be concluded that the social security construction in the Islamic economic system has four stages, namely: (1) guarantees the individual against himself (individual guarantees); (2) among individuals with his family (family guarantees); (3) individuals with society (assurance society); and (4) between people within a country (a guarantee). Therefore, the construction of social security system in Islamic economics illustrates that guarantee it in layers. When social security was able to be resolved by the individual, then simply at the level of the individual. But when could not be resolved at the level of the individual, it will be resolved at the level of the family. If not completed in level of the family, it will be resolved at the community level. If social security did not complete in the community, then the obligation of the State to finish itArtikel ini bermaksud untuk mengkaji sistem jaminan sosial dalam perspektif ekonomi Islam. Dengan menggunakan literature review, artikel ini membedah jaminan sosial Islam. Artikel ini menyimpulkan bahwa konstruksi jaminan sosial dalam ekonomi Islam memiliki empat sistem tahapan, yaitu: (1) jaminan individu terhadap dirinya (jaminan individu); (2) antara individu dengan keluarganya (jaminan keluarga); (3) individu dengan masyarakatnya (jaminan masyarakat); dan (4) antara masyarakat dalam suatu negara (jaminan negara). Oleh karena itu, konstruksi sistem jaminan sosial dalam ekonomi Islam menggambarkan bahwa jaminan itu berlapis-lapis. Apabila jaminan sosial mampu diselesaikan oleh individu, maka cukup di level individu. Apabila tidak bisa diselesaikan di level individu, maka akan diselesaikan di level keluarga. Apabila tidak selesai di level keluarga, maka akan diselesaikan di level masyarakat. Apabila jaminan sosial tidak selesai di masyarakat, maka kewajiban negara menyelesaikannya.